Tsunami deposit associated with the 2011 Tohoku‐oki tsunami in the Hasunuma site of the Kujukuri coastal plain, Japan. (29th September 2016) - Matsumoto, Dan; Sawai, Yuki; Tanigawa, Koichiro; Fujiwara, Osamu; Namegaya, Yuichi; Shishikura, Masanobu; Kagohara, Kyoko; Kimura, Haruo
Abstract: We describe the detailed sedimentary characteristics of a tsunami deposit associated with the 2011 Tohoku‐oki tsunami in Hasunuma, a site on the Kujukuri coastal plain, Japan. The thick tsunami deposit was limited to within 350 m from the coastline whereas the inundation area extended about 1 km from the coastline. The tsunami deposit was sampled by excavation at 29 locations along three transects and studied using peels, soft‐X imaging and grain‐size analysis. The deposit covers the pre‐existing soil and reached a maximum measured thickness of 35 cm. It consists mainly of well‐sorted medium to fine sand. On the basis of sedimentary structures and changes in grain size, we divided the tsunami deposit into several sedimentary units, which may correspond to multiple inundation flows. The numbers of units and their sedimentary features vary among the three transects, despite the similar topography. This variation implies a considerable influence of local effects such as elevation, vegetation, microtopography, and distance from footpaths, on the tsunami‐related sedimentation. Abstract : This article reports detailed description of a 2011 Tohoku‐oki tsunami deposit in the Hasunuma site, such as thickness, sedimentary structures and grain‐size distribution. We discuss lateral and vertical changes of such characteristics, and relationship with the sedimentation by the tsunami inundation flows.